(untitled) (Tintas: Quaderni di Letterature iberiche e iberoamericane, 2021)
In ancient Biblical, Greco-Roman, and Egyptian traditions, the most famous male sibling pairs are mortal enemies. What about the sisters? This article gives prominence to the figure of the mythical sister and highlights how the polysemic characteristics of sisterhood can generate multiple meanings ranging from rivalry to alliance. From this starting point, my study directs its gaze towards the 20th-century Latin American rewritings of sisterhood myths. I investigate the new forms that the ancient dynamic rivalry/alliance takes in these rewritings and reflect on the new meanings that the dynamic acquires in 20th-century Latin American socio-political contexts. A case study from Cuba serves as an example of the resignification of the rivalry/alliance between sisters. I read the novel Las hermanas Agüero (1997) by the Cuban-American writer Cristina García in dialogue with the Greek myth about Helios (the Sun) and his sisters Selene (the Moon) and Eos (the Dawn). The novel gives protagonism to a female Helios and emphasizes the transformation of the rivalry between two opposing sisters into a cross-border alliance. To that effect, Las hermanas Agüero gives a central role to a hybrid figure who serves as an intermediary. In this way, the novel calls into question a system that pigeonholes women into opposed models and shows a possible path to different and more ambivalent perceptions of femininity. The novel thus endows sisterhood with a meaning related to the re-modelling of femininity in the Cuban and Cuban-American 20th-century society.